Avian influenza A (H9N2): computational molecular analysis and phylogenetic characterization of viral surface proteins isolated between 1997 and 2009 from the human population - Butt, Azeem M (BioMed Central, 2010)
BACKGROUND: H9N2 avian influenza A viruses have become panzootic in Eurasia over the last decade and have caused several human infections in Asia since 1998. To study their evolution and zoonotic potential, we conducted an in silico analysis of H9N2 viruses that have infected humans between 1997 and 2009 and identified potential novel reassortments. RESULTS: A total of 22 hemagglutinin (HA) and neuraminidase (NA) nucleotide and deduced amino acid sequences were retrieved from the NCBI flu database. It was identified that mature peptide sequences of HA genes isolated from humans in 2009 had glutamine at position 226 (H3) of the receptor binding site, indicating a preference to bind to the human α (2-6) sialic acid receptors, which is different from previously isolated viruses and studies where the presence of leucine at the same position contributes to preference for human receptors and presence of glutamine towards avian receptors. Similarly, strains isolated in 2009 possessed new motif R-S-N-R in spite of typical R-S-S-R at the cleavage site of HA, which isn't reported before for H9N2 cases in humans. Other changes involved loss, addition, and variations in potential glycosylation sites as well as in predicted epitopes. The results of phylogenetic analysis indicated that HA and NA gene segments of H9N2 including those from current and proposed vaccine strains belong to two different Eurasian phylogenetic lineages confirming possible genetic reassortments. CONCLUSIONS: These findings support the continuous evolution of avian H9N2 viruses towards human as host and are in favor of effective surveillance and better characterization studies to address this issue.